ANALYSIS OF CURVED EDGE PLATES BY THE BOUNDARY-ELEMENT METHOD - Neto, L. D.; Depaiva, J. B. (Elsevier B.V., 1993)
The aim of this work is to present a formulation of the boundary element method to analyse elastic and isotropic plates with curved boundaries. In this study the plate boundary is approximated, along each element, by a second degree polynomial relation or by a circular arch, in order to better represent the real boundary. The numerical integration is performed by the self-adaptive coordinate transformation proposed by Telles. The effective shear forces are approximated by concentrated reactions applied at the boundary element nodes, according to the alternative formulation introduced by Paiva. Some examples are presented to demonstrate the better accuracy obtained with the proposed elements.
Keywords: BOUNDARY ELEMENT METHOD; BENDING PLATES; CIRCULAR ARCH ELEMENT